A 3-weekly schedule of irinotecan and panitumumab for wild-type KRAS metastatic colorectal cancer. (April 2014) - Hansen, Torben Frøstrup; Andersen, Rikke Fredslund; Pallisgaard, Niels; Spindler, Karen-Lise Garm; Pløen, John; Keldsen, Nina; Lindebjerg, Jan; Sørensen, Flemming Brandt; Jakobsen, Anders
SUMMARY : Aim: We investigated the combination of irinotecan and panitumumab as a 3-weekly schedule in patients with wild-type KRAS metastatic colorectal cancer, who had progressed after standard chemotherapy.Material & methods: Patients received concomitant irinotecan (350 mg/m 2 ) and panitumumab (9 mg/kg) once every 3 weeks. The primary end point was response rate. Secondary end points included progression-free survival (PFS), overall survival (OS) and translational research.Results: Inclusion was stopped early owing to lack of efficacy (n = 31). The response rate was 16%, median PFS and OS was 2.0 months (95% CI: 1.9–4.0) and 7.8 months (95% CI: 4.6–8.8), respectively. The most commonly encountered adverse event was skin rash (84% any grade). Pretreatment cell-free DNA levels were significantly related to disease control (p = 0.04), PFS (p = 0.04) and OS (p = 0.002), respectively.Conclusion: The present treatment regimen was less effective than expected and is not recommended. The clinical importance of cell-free DNA deserves further research.